Efek Pemilu Presiden Terhadap Volume Perdagangan Saham di Pasar Modal Indonesia - Permata, Citra Puspa; Ghoni, Muhammad Abdul (Disclosure: Journal of Accounting and Finance, 2021)
The â€œreason for this research is to see the average difference of stock trading volume activity after and before the implementation of the Presidential Election. This research uses an event study, where the research is conducted for 7 working days after up to 7 working days before the implementation of the presidential election. This study uses additional information obtained from the Indonesia Stock Exchange. The information used in this test includes a list of LQ45 shares, daily trading volume, and number of shares outstanding. While the samples used are stocks that are included in the LQ45 list on the Indonesia Stock Exchange.â€The results showed that from the results of statistical tests on the average difference of stock trading volume activity after and before the implementation of the presidential election, there was a significant difference to the average stock trading volume activity after and before the implementation of the presidential election.